Damage control : Media representation and responses to police deviance - J. Chan (Law Text Culture, 1995)
This paper examines the processes and outcomes of the negotiation of public discourse between the police and the media when police organisations are called to account in public scandals. Using the 1992 television documentary Cop It Sweet as a case study, the paper describes the problems of police/Aborigines relations exposed in the film, the reaction within the police hierarchy, the attempt at damage control and the subsequent repair work carried out in tenns of improving police/minority relations. The role of the media as an agent of criminal justice reform and a mechanism for demanding police accountability is discussed in this context. It will be argued that scandals force police organisations to provide a credible account that deviance is under control. The consequences of scandals depend on the nature of the police organisation and its commitment to reform. Public discourse in relation to police deviance may provide an opportunity for police reformers to further their reform agenda, but in an organisation less committed to change, there is a danger that scapegoating, band-aid repair work and cosmetic changes may substitute for meaningful reform. The irony of police reform is that commitment to openness and accountability does not necessarily lead to a positive police image, but continual damage-control work by upper management in relation to scandals may lead to further cynicism and a hardening of the 'street cop' culture.